Sham-Chewing in Sows Is Associated With Decreased Fear Responses in Their Offspring - Tatemoto, Patricia; Bernardino, Thiago; Alves, Luana; Zanella, Adroaldo José (Frontiers in Veterinary Science, 2019)
The hypothesis is that sham-chewing expressed by the mother during gestation affects fetus programming. The goal was to assess the effects of maternal sham-chewing on offspring welfare indicators, such as behavior and physiology. Sows that exhibited consistent sham-chewing on least two of six days of observation (N = 7) were compared with sows that never exhibited sham-chewing (non-sham-chewing sows; N = 4) in these six days. Salivary cortisol from sows and piglets were analyzed for assessing hypothalamic pituitary adrenal (HPA) axis activity, since cortisol is a physiological indicator of welfare. Moreover, placental tissue was collected to assess cortisol and cortisone concentration. Piglets’ behaviors and fear tests were performed after weaning (one couple per sow). In the fear tests, behaviors were collected in an open field test to determine states of fear indicators. Non-sham-chewing sows had lower concentrations of cortisol on days 91 and 92 of gestation, on the morning. Moreover, placental cortisol was greater among sham-chewing than non-sham-chewing sows, which the levels were higher in sows that exhibited sham-chewing. In the open field test, piglets born from non-sham-chewing sows demonstrated more latency to move in the arena and less activity, indicating more fear. Based in our data, we concluded that maternal sham-chewing expression is related to less fear in their offspring. Although stereotypies has been studied, attention has not been devoted to the effects of the prenatal period in considering a fetal reprogramming approach.